2011
DOI: 10.1080/10887156.2011.570140
|View full text |Cite
|
Sign up to set email alerts
|

Do the behaviors related to managerial effectiveness really change with organizational level? An empirical test.

Abstract: Kaiser, Craig, Overfield, & Yarborough, this issue). However, there is a noteworthy gap in this otherwise extensive literature. Because job requirements vary with organizational level, it seems logical to suppose that the behaviors that constitute effective performance also differ across levels. But, as Zaccaro (2001) andYukl (2006) have pointed out, the published literature contains no direct empirical tests of the proposition that the behaviors that predict managerial effectiveness vary with organizational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…In this regard, other studies also confirm the importance of demographic features such as gender, experience (Muchiri et al, 2011;Wickramasinghe and De Zoyza, 2008), education (Igbaria et al, 1989;gbaria and Nachman, 1990) levels/positions (Baral and Bhargava, 2011;Kaiser and Craig, 2011;Mumford, et al, 2007;Rai, 2009) on preferences, attitude and behaviors. Our next research question, thus, considers the importance of demographic variations…”
Section: Demographic Variations and Hrismentioning
confidence: 78%
“…In this regard, other studies also confirm the importance of demographic features such as gender, experience (Muchiri et al, 2011;Wickramasinghe and De Zoyza, 2008), education (Igbaria et al, 1989;gbaria and Nachman, 1990) levels/positions (Baral and Bhargava, 2011;Kaiser and Craig, 2011;Mumford, et al, 2007;Rai, 2009) on preferences, attitude and behaviors. Our next research question, thus, considers the importance of demographic variations…”
Section: Demographic Variations and Hrismentioning
confidence: 78%
“…As previously identified, schools operate with a clear management structure wherein school boards empower superintendents who task principals which depend on teachers to ensure that the mission of the school is fulfilled on a yearly basis. Given that those individuals serving as principals bear the responsibility of enacting the reforms in a non-abrasive manner (Kaiser & Craig, 2011), that reform implementation has a greater chance of success within a culture of trust (Louis & Wahlstrom, 2011), and that the changes brought on by reform are frequently viewed as unnecessary shifts away from the familiar (Evans, 1993), the principal within any given school faces an enormous challenge when seeking to implement reform of any kind within the walls of a school. Virgilio and Virgilio (1984) verify such sentiment in their claim that "the success or failure in implementing [reform] falls heavily on the shoulders of the school principal" (p. 346).…”
Section: The Principal's Role In Reformmentioning
confidence: 99%
“…Throughout the reform implementation process, the usage of communication by the individuals involved becomes a key aspect to the success of the reform efforts (Patterson & Czajkowski, 1979;Evans, 2005;Kaiser & Craig, 2011;Virgilio & Virgilio, 1984). Specifically, the type of communication and the frequency of communication hold great impact on reform efforts.…”
Section: The Principal's Role In Reformmentioning
confidence: 99%
“…In a study of executives, middle managers, and supervisors, Kaiser and Craig (2011) found that learning agility was the only factor that predicted success across all three career levels. However, learning agility was a stronger predictor of success for executives than it was for middle managers and supervisors.…”
Section: Learning Agility and Performancementioning
confidence: 99%